THE COMPARISON OF OXIDATIVE STRESS LEVELS BETWEEN E-CIGARETTE SMOKERS AND CONVENTIONAL SMOKERS IN YOUNG ADULT IN SURABAYA - Elisabeth Tri Wahyuni; Helmia Hasan (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Smoking is one of the leading causes of morbidity and mortality worldwide. Previously, e-cigarettes were considered safe, but later some studies have reported that e-cigarette can increase oxidative stress and induce an inflammatory response. Isoprostane is a biomarker of oxidative stress, which is thought to play a role in the pathogenesis of COPD. The purpose of this study was to determine the level of oxidative stress between e-cigarette and conventional smokers by measuring the isoprostan level in the two group and comparing them. Method: This research is an observational analytic study conducted in Surabaya. Anamnesis, physical examination, chest X-ray, and complete blood were carried out, followed by urine isoprostane. The research subjects were 28 e-cigarrete smokers, 27 conventional smokers, and 14 controls who never smoked. Urine isoprostane levels were measured by the ELISA method using a random urine sample and then corrected with urine creatinine from the same sample. Differences in urine isoprostane levels in the three groups used the Mann-Whitney test. Result: The statistical analysis results showed no significant difference in urine isoprostane levels between e-cigarette and conventional smokers (p = 0.054). The mean and median of urine isoprostane in e-cigarette and conventional smokers tended to be higher than controls. Conclusion: The levels of urine isoprostane for e-cigarette and conventional smokers tended to be higher than controls, but there was no statistically significant difference. It can be concluded that the level of oxidative stress in the two groups did not have significant difference but tended to be higher than controls.